Surgical Management of Impacted Supernumerary Tooth and Odontome under General Anesthesia in an Emotionally Immature Child: A Case Report - Rasleen Dua; Pallavi Vashisth; N. Sathyajith Naik; Sriparna De (Indian Journal of Dental Sciences)
The disorder known as hyperdontia is characterized by an excess of teeth or teeth that appear to be added to the normal amount of teeth. With a frequency ranging from 0.1% to 3.9% in permanent dentition and from 0.3% to 1.8% in deciduous dentition, it affects males more often than women. Since children’s cognitive abilities are still developing in comparison to adults’, children freely communicate their worry and anxiety and frequently exhibit uncooperative behavior patterns while undergoing treatment. A 7-year-old child who was emotionally immature reported with a principal complaint of missing tooth in his left upper front tooth area for 2 years. Cone-beam computed tomography was advised to verify location and structural interaction with neighboring structures. Due to his lack of emotional sensitivity and cooperation with others, we planned the surgical extraction under general anesthesia. In the present case, it was deemed preferable to wait for a spontaneous eruption, and the patient was observed for a month on a regular basis.